Neurogenetic and Neuroepigenetic Mechanisms in Cognitive Health and Disease - Coda, Davide Martino; Gräff, Johannes (Frontiers in Molecular Neuroscience, 2020)
Over the last two decades, the explosion of experimental, computational and high-throughput technologies has led to critical insights into how the brain functions in health and disease. It has become increasingly clear that the vast majority of brain activities result from the complex entanglement of genetic factors, epigenetic changes and environmental stimuli, which, when altered, can lead to neurodegenerative and neuropsychiatric disorders. Nevertheless, a complete understanding of the molecular mechanisms underlying neuronal activities and higher order cognitive processes continues to elude neuroscientists. Here, we provide a concise overview of how the interaction between the environment and genetic as well as epigenetic mechanisms shapes complex neuronal processes such as learning, memory and synaptic plasticity. We then consider how this interaction contributes to the development of neurodegenerative and psychiatric disorders, and how it can be modelled to predict phenotypic variability and disease risk. Finally, we outline new frontiers in neurogenetic and neuroepigenetic research, and highlight the challenges these fields will face in their quest to decipher the molecular mechanisms governing brain functioning.